Performance comparison of single-mode single-cladding thulium doped and thulium/holmium co-doped fiber lasers in ring cavity - Shamsudin, H.; Latiff, A.A.; Razak, N.N.; Jusoh, Z.; Ahmad, Harith; Harun, Sulaiman Wadi (National Institute of Optoelectronics, 2016)
We investigate and compare the performance of the thulium-doped fiber laser (TDFL) and thulium holmium co-doped fiber laser (THDFL) based on 800 nm pumping. Both fiber lasers generated a broadband amplified spontaneous emission (ASE) across a wavelength range of 1720-2010 nm, with a threshold pump power of 155.58 mW. The THDFL and the TDFL are operating at single wavelength of 1908.87 nm and at dual wavelength of 1931.62 nm and 1937.09 nm respectively with a signal-to-noise ratio (SNR) of more than 30 dB. We also discuss the cross-relaxation process for TDFL and energy transfer for THDFL operations. With 1550 nm pumping, the THDFL operates at 1986.4 nm due to energy transfer from Tm3+ to Ho3+ in the active medium.